Implementasi Penggunaan Dana Stimulan terhadap Partisipasi Masyarakat pada Program BBGRM di - gewe, dwi rizka witria; Frinaldi, Aldri; Asnil, Asnil (Jurnal Ilmiah Wahana Pendidikan, 2023)
Manunggal is a development system implemented in an integrated manner between the government, TNI/POLRI and the community in order to speed up the development process. Community Mutual Cooperation Service Month is a national movement in the context of strengthening social integration, national integration in order to strengthen unity through empowerment and preserving the values ​​of mutual cooperation as well as increasing the active role of society in development. In the ongoing implementation of the BBGRM Manunggal program, it was found that there were still problems with the low number of community participation, which ultimately affected the realized value and quality of the infrastructure development carried out. The research method used is a qualitative approach. Based on the research results, it shows the lack of community self-funding. The conclusion that the author found based on the results and discussion of the research above found that in general the BBGRM Manunggal program can be said to be successful in building infrastructure that meets community needs. However, the stimulant funds used in this program cannot be said to be effective in increasing community participation, this is evidenced by the lack of role from the community.